Penyebab malas belajar siswa sekolah dasar: kajian pustaka (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
This paper discusses the causes of laziness in learning among elementary school students through a literature‑based (desk study) approach. Using 14 scientific references, the study classifies the causes into internal factors such as limited cognitive abilities, low motivation, poor self‑regulation, fear of failure, negative mood, and unhealthy lifestyle, and external factors such as ineffective teaching methods, parental neglect, unsupportive school climate, peer influence, and excessive use of social media and digital devices. The analysis reveals that laziness is not simply personal weakness but a complex consequence of cognitive, emotional, social, and contextual interaction. The article concludes that addressing laziness in learning requires a holistic strategy, integrating pedagogical adjustments, parental involvement, emotional support, and habit‑forming learning routines. This study is expected to provide a theoretical basis for teachers, parents, and educational practitioners in designing interventions to reduce academic laziness and improve elementary students’ learning engagement